A Study on the Behaviour of Total Carbon and Dissolved Organic Carbon in Groundwaters of Pondicherry Region, India - Thilagavathi, R.; Chidambaram, S.; Thivya, C.; Prasanna, Mohan Viswanathan; Pethaperumal, S.; Tirumalesh, K. (CAFET-INNOVA Technical Society, Hyderabad, India, 2014)
Organic carbon concentrations can vary considerably, both spatially and temporally, so a large number of analyses are frequently required to produce a representative estimate of concentrations. Natural organic carbon is mainly derived from decomposing vegetation and other organic matter in the soil zone. In this scenario, a baseline attempt was made to study the behaviour of organic carbon content in groundwater by collecting samples from the layered aquifer sequence of Pondicherry. The samples were collected from Recent Alluvium (30), Upper Cuddalore(13), Lower Cuddalore (13), Other Tertiary formation (7), Mixed aquifer (5) and Cretaceous formations (24). The analysis of these samples show that higher concentration of Dissolved Organic Carbon (DOC) was noted in the Alluvial formation and the average concentration was higher in Upper Cuddalore Formation. The samples of these formations were compared with pH, Ionic strength, and log pCO2 and bicarbonate concentration. The alluvial aquifer shows that pH governed dissolution along the coastal tracts and in Upper Cuddalore formation it’s based on interaction between aquifer matrix and groundwater.